A High-Throughput Droplet-based Method to Facilitate Microbial Conjugation - Monica Chu; Jose Wippold; Rebecca Renberg; Margaret Hurley; Bryn Adams; Arum Han (Bio-Protocol)
Droplet microfluidic platforms have been broadly used to facilitate DNA transfer in mammalian and bacterial hosts via methods such as transformation, transfection, and conjugation, as introduced in our previous work. Herein, we recapitulate our method for conjugal DNA transfer between Bacillus subtilis strains in a droplet for increased conjugation efficiency and throughput of an otherwise laborious protocol. By co-incubating the donor and recipient strains in droplets, our method confines cells into close proximity allowing for increased cell-to-cell interactions. This methodology is advantageous in its potential to automate and accelerate the genetic modification of undomesticated organisms that may be difficult to cultivate. This device is also designed for modularity and can be integrated into a variety of experimental workflows in which fine-tuning of donor-to-recipient cell ratios, growth rates, and media substrate concentrations may be necessary.